1984
DOI: 10.2355/isijinternational1966.24.808
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Rate of Iron Oxide in Molten Slag by Carbon in Molten Iron

Abstract: SynopsisIn the research of a continuous ironmaking process from reduced iron, or pre-reduced iron ore, the reduction rate of iron oxide in molten slag by carbon in molten iron was investigated to know the optimum condition. Mixture consisted of, mainly, 40g master slag and 17.1 g iron oxide, was added onto the molten iron in a graphite crucible, the molten copper in a graphite crucible, or the molten iron in an almina crucible to measure the amount of CO gas evolved in the range of 1320 N 1 620 °C. The followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…MacRae 29 reduced solid iron oxide in an iron carbon melt at different temperatures. Sato et al 30,31 also studied the SR of molten iron oxide by a carbon saturated iron bath and found that the reduction rate was proportional to the second power of iron oxide concentration in the molten slag except the initial and final periods and the maximum rate was attained at a lime/silica ratio of about 1?5. They also calculated the apparent activation energies of the slag-graphite and slag-metal reactions at various CaO/SiO 2 ratios.…”
Section: Reduction By Solute Carbonmentioning
confidence: 99%
“…MacRae 29 reduced solid iron oxide in an iron carbon melt at different temperatures. Sato et al 30,31 also studied the SR of molten iron oxide by a carbon saturated iron bath and found that the reduction rate was proportional to the second power of iron oxide concentration in the molten slag except the initial and final periods and the maximum rate was attained at a lime/silica ratio of about 1?5. They also calculated the apparent activation energies of the slag-graphite and slag-metal reactions at various CaO/SiO 2 ratios.…”
Section: Reduction By Solute Carbonmentioning
confidence: 99%
“…The movements of reactants and products at the interface are affected by several factors and control the rate of reduction. There have been a few investigations reported in the literature on smelting reduction of iron oxide in contact with Fe‐C melts 5–8, mostly in slag phase 9–21. However, fundamental studies on smelting reduction of iron ore‐coal composite pellets in liquid metal bath are not available in the published literature.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20][21][22] Paul et al [17] concluded that for slags with less than 5 mass pct FeO, the rate of reduction by Fe-C droplets is controlled by mass transfer of FeO in the slag plus a chemical reaction at the gas-metal interface. For slags with more than 40 mass pct FeO, the reduction rate is controlled by a chemical reaction either at the gas/metal interface or at the gas/slag interface.…”
Section: Introductionmentioning
confidence: 99%